The growth of the liberal soul - Walsh, David (Univ. of Missouri Press, 1997)
In The Growth of the Liberal Soul, David Walsh confronts a core difficulty of the liberal democratic tradition in explaining and justifying itself. Acknowledging the incompleteness of liberal order as a theoretical explication of its underlying beliefs, Walsh analyzes contemporary debates about the foundations of liberal democratic politics. The widespread abandonment of the search for foundations by John Rawls, Richard Rorty, Michael Oakeshott, and the deconstructionists has been interpreted as signifying the absence of any sustaining inner resources. The result has been the confusion of contemporary liberal democratic self-understanding, which cannot make sense of its own extraordinary historical success nor apparently prevent the evident unraveling of its own moral code. It is this state of crisis from which Walsh's study takes its point of departure